Analysis of Cropland Changes in the Arid Northwest Region of China - A Case Study of Yulin City - Yang, Liangyan; Ye, Shenglan (International Journal of Agriculture and Food Sciences Research, 2025)
Utilizing land use/land cover (LULC) remote sensing monitoring data from China for the 1980s, 2000, and 2018, this study investigated the patterns and driving forces of cropland change in Yulin City through the application of a land use transfer matrix. The results indicated that the cropland area initially increased and then decreased, a trend closely associated with national ecological policies. Cropland changes in Yulin City were influenced by both natural and socio-economic factors, with ecological policies and urbanization development playing dominant roles.